Analysis on Nutrient Contents & Food Safety of Local Gatul Fish (Xiphophorus hellerii) as Potential Food Resources - Dwi Rahayu; Miftahul Jannah; Saibatul Linadziroh; Dwi Litsyorini (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2022)
Gatul fish is one abundance of freshwater introduced fish that can be found in all tropical and subtropical area. One species of Gatul fish has been found in Telaga Sari, Pasuruan Regency is Xiphophorus hellerii. This fish are live bearers, dimorphism sexual, modification of anal fish called gonopodium and pregnant & birthing female. Until now, its potential as a food resource is not known. This research aimed to analyze nutrient contents of Gatul fish as food resources based on the protein and fat content and to evaluate the food safety based on the content of plumbum, cadmium, and mercury. The sample of Gatul fish was collected from Telaga Sari based on four Xiphophorus helleri (female and male). The protein content was analyzed using Kjeldahl method, while the content of fat was analyzed using soxhlet method. In addition, the level of plumbum, cadmium, and mercury in the flesh Gatul fish were tested using atomic adsorption spectroscopy (AAS). The results showed that both of the flesh Gatul fish (male and female) contained high protein for orange male (20.389±0.238); orange female (20.256±0.07); gray male (21.3557±0.25), and gray female (20.5687±0.10) respectively. The fat of flash Gatul Fish both male and female content in Gatul fish ranged from 2.966%-3.934%. It seems that the nutrient content outweighs the content of others commercial consumed fish. The content of plumbum in the flesh fish were 0.712±0.0116 ppm; chadmium were 0.128±0.129, Meanwhile, the content of mercury in the flesh fish were 0.0039±0.0017. These numbers are considerably lower that the level permitted. Hence, it can be concluded that Gatul fish has potency as a cheap, safe, and nutritious of food resource